An Overview of Nanotechnology in Food Science: Preparative Methods, Practical Applications, and Safety. (29th October 2018) - Yu, Hyunjong; Park, Jun-Young; Kwon, Chang Woo; Hong, Sung-Chul; Park, Kyung-Min; Chang, Pahn-Shick
Abstract : As the researches to utilize nanotechnology in food science are advanced, applications of nanotechnology in various fields of the food industry have increased. Nanotechnology can be applied to the food industry for production, processing, storage, and quality control of foods. Nanomaterials, unlike conventional microscale materials, having novel characteristics can improve sensory quality of foods by imparting novel texture, color, and appearance. Nanotechnology has been used to design nanosensors for detection of harmful components in foods and a smart packaging system enabling to recognize food contamination very rapidly and sensitively. Nanoencapsulation is the most significant technology in food science, especially for bioactive compounds and flavors. Targeted delivery systems designed with nanoencapsulation can enhance bioavailability of bioactive compounds after oral administration. In addition, nanoencapsulation enables to control the release of flavors at the desired time and to protect the degradation of flavors during processing and storage. In this review, current applications of nanotechnology in food science including flavor control, enhancement of bioavailability of bioactive compounds, and detection of deleterious substances in foods are presented. Furthermore, this article overviews classification, preparative methods, and safety issues of nanomaterials for food science. This review will be of help to provide comprehensive information for newcomers utilizing nanotechnology to the food sector.